2020
DOI: 10.31083/j.rcm.2020.03.62
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of left atrial appendage occlusion in atrial fibrillation patients with chronic kidney disease: a systematic review and meta-analysis

Abstract: Atrial fibrillation (AF) is the most common arrhythmia among the elderly, and more frequently occur in those with chronic kidney disease (CKD). Left atrial appendage occlusion (LAAO) is used as a mechanical alternative approach for prevention of AF-related thromboembolisms. This meta-analysis was conducted to provide suggestions for the clinical application of LAAO in AF patients with CKD. The incidence of perioperative adverse events and other clinical effects after operation was by a single rate meta-analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
(33 reference statements)
1
6
0
3
Order By: Relevance
“…Following that, articles are fairly narrowed and screened by their titles or abstracts using the inclusion/exclusion criteria. Finally, articles underwent quality assessments, and the eligible reports came down to a total of eight articles [3,5,7,[8][9][10]12,13]. Figure 2 shows an in-depth overview of the process adopted, namely identification, screening, and the inclusion of articles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following that, articles are fairly narrowed and screened by their titles or abstracts using the inclusion/exclusion criteria. Finally, articles underwent quality assessments, and the eligible reports came down to a total of eight articles [3,5,7,[8][9][10]12,13]. Figure 2 shows an in-depth overview of the process adopted, namely identification, screening, and the inclusion of articles.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it could be a safer option for younger groups. More studies need to be done on this matter to opine further [ 13 ]. Table 3 provides a summary of all the articles discussed in this section.…”
Section: Reviewmentioning
confidence: 99%
“…42 A meta-analysis conducted by Zhang, found almost the same ratio (HR: 2.0) as our results. 43 It is remarkable that HASBLED was identified as an independent predictor of death in the A-CKD cohort. These findings should be taken into account when LAAO is considered in these patients.…”
Section: Discussionmentioning
confidence: 98%
“…The available data suggest that direct oral anticoagulants have a better safety and efficacy profile in patients with CKD, but data in patients with advanced CKD are scarce [ 50 ]. On the other hand, left atrial appendage occlusion has been shown to reduce the incidence of thromboembolic events in patients with AF, with a low incidence of adverse events, so this strategy should be considered for patients with an increased risk of bleeding [ 51 ].…”
Section: Definition and Objectivesmentioning
confidence: 99%